ANALISIS KINERJA KEUANGAN DAERAH DI PROVINSI SULAWESI UTARA TAHUN 2014 – 2019 - Rilmonth Manueke, Billy Boy (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to determine the extent of regional financial performance in North Sulawesi Province based on the regional fiscal decentralization ratio, regional financial dependency ratio, regional financial independence ratio, regional financial effectiveness ratio and regional financial capability ratio. The analysis shows the calculation of the degree of fiscal decentralization ratio, the ratio of regional financial dependency, the ratio of regional financial independence, the ratio of effectiveness of PAD and the ratio of financial growth of the North Sulawesi Provincial Government for the period 2014 - 2019. Financial Performance of the North Sulawesi Provincial Government is still considered to be very poor when viewed with using Fiscal Decentralization Degree Ratio. This is because the average ratio is still in the interval> 25% - 50%. The Financial Performance of the North Sulawesi Provincial Government is still classified as moderate when viewed using the Regional Financial Dependency Ratio. The Financial Performance of the North Sulawesi Provincial Government is still relatively low when viewed using the Regional Financial Independence Ratio. The financial performance of the North Sulawesi Provincial Government can be categorized as effective if seen using the PAD Effectiveness Ratio. The Financial Performance of North Sulawesi Provincial Government when seen from the PAD Growth Ratio grew positively. The average growth was 8.69% when compared to the realization of total regional expenditure.